2009
DOI: 10.1080/09553000802635054
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of radon: A review of the literature

Abstract: Radon is an established human lung carcinogen based on human epidemiological data supported by experimental evidence of mutagenesis studies in cell culture and laboratory animals. Extrapolation from cohort studies on miners suggested that radon is the second leading cause of lung cancer death after tobacco smoke. The majority of studies on the relationship between radon and other types of cancers showed weak or no association. Low levels of radon can be found in drinking water; however, radon released during w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(109 citation statements)
references
References 99 publications
0
90
0
3
Order By: Relevance
“…Using various modeling approaches, results of lung cancer risk in miners were used to project lung cancer risk for general population exposed to residential radon. However, such direct extrapolation from these studies is uncertain because of the major differences between working in underground conditions and living in houses (Al-zoughool and Krewski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Using various modeling approaches, results of lung cancer risk in miners were used to project lung cancer risk for general population exposed to residential radon. However, such direct extrapolation from these studies is uncertain because of the major differences between working in underground conditions and living in houses (Al-zoughool and Krewski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Once inhaled, they deposit in lungs causing severe health effects (WHO, 2010). There is direct evidence from residential epidemiological studies that radon causes lung cancer, even at concentrations typically found in indoor air (Al-Zoughool & Krewski, 2009). Some studies suggested also an association with other cancers, in particular leukaemia and cancers of the extra-thoracic airways (WH0, 2010).…”
Section: Radonmentioning
confidence: 99%
“…Other studies show that radon exposure in miners induces gene mutations and chromosomal aberrations. Numerous in vitro cytogenetic studies demonstrated that radon induces different types of genetic and cytogenetic damage that is likely to play a role in radon lung carcinogenesis (Al-Zoughool & Krewski, 2009). …”
Section: Carcinogenic and Mutagenic Effectsmentioning
confidence: 99%